Bus Navigation System with Effective Data Transmission Using GPS and Wireless Transmitter (International Journal of Engineering and Computer Science, 2014)
Global positioning system (GPS) is being actively employed in a variety of vehicular monitoring systems such as automated car navigation and emergency assistance. Nowadays easily observed many passengers footed at the Bus stops waiting for the bus. This paper considers performance issues in Public transport monitoring system that utilize GPS and embedded system. For the purpose of monitoring the movement of the bus, to report the location of the bus in the bus stop and to record whether the bus stops in its respective bus stop using Global Positioning system in collaboration with Transceivers modules, and detect any passenger stands in footboard is described here. In addition to some basic functions such as real-time monitoring, some special functions are combined to make the system compatible with the daily operations of any public transport scheme. The proposed method will surely provide smooth and linear transmission of location information to the bus stations which led people to take decision either to wait for Bus or not.